2015
DOI: 10.1073/pnas.1501554112
|View full text |Cite
|
Sign up to set email alerts
|

Coincidental loss of DOCK8 function in NLRP10-deficient and C3H/HeJ mice results in defective dendritic cell migration

Abstract: Dendritic cells (DCs) are the primary leukocytes responsible for priming T cells. To find and activate naïve T cells, DCs must migrate to lymph nodes, yet the cellular programs responsible for this key step remain unclear. DC migration to lymph nodes and the subsequent T-cell response are disrupted in a mouse we recently described lacking the NOD-like receptor NLRP10 (NLR family, pyrin domain containing 10); however, the mechanism by which this pattern recognition receptor governs DC migration remained unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 37 publications
5
71
1
Order By: Relevance
“…For example, the N-ethyl-N-nitrosoureamediated mutagenesis in mice has shown that DOCK8 plays an important role in B cell immunological synapse and long-lasting humoral immunity and also contributes to the development or survival of memory CD8 ϩ T cells (15)(16)(17). Furthermore, by generating DOCK8-deficient (Dock8 Ϫ/Ϫ ) mice, we and others have revealed that DOCK8 is required for DCs to migrate effectively within 3D, but not 2D, microenvironments (9,18). However, DOCK8 deficiency in DCs did not affect the global Cdc42 activation induced by chemokine stimulation (9).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…For example, the N-ethyl-N-nitrosoureamediated mutagenesis in mice has shown that DOCK8 plays an important role in B cell immunological synapse and long-lasting humoral immunity and also contributes to the development or survival of memory CD8 ϩ T cells (15)(16)(17). Furthermore, by generating DOCK8-deficient (Dock8 Ϫ/Ϫ ) mice, we and others have revealed that DOCK8 is required for DCs to migrate effectively within 3D, but not 2D, microenvironments (9,18). However, DOCK8 deficiency in DCs did not affect the global Cdc42 activation induced by chemokine stimulation (9).…”
mentioning
confidence: 86%
“…Ϫ/Ϫ BM-derived DCs migrate normally on 2D surfaces, they fail to migrate effectively within 3D extracellular matrix scaffolds such as collagen gels (9,18). To examine the role of LRAP35a in DC migration, we also knocked down LRAP35a expression in Dock8 ϩ/Ϫ BM-derived DCs (Fig.…”
Section: Role Of Lrap35a In DC Migration In 2d and 3d Environmentsaltmentioning
confidence: 99%
“…A contrasting pro-inflammatory role for NLRP10 has also been implicated through a study of Shigella flexneri infection, in which NLRP10 contributed to inflammatory cytokine release, possibly by interacting with NOD1 and its down-stream pathway components (9). Although NLRP10 was implicated in adaptive immune responses through the regulation of dendritic cell migration, recent studies revealed a coincident mutation in DOCK8 in NLRP10-deficient mice, and suggested that DOCK8 was responsible for the observed phenotype (10). Thus, the functions of NLRP10 in innate immunity need further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, DOCK8 regulates Cdc42 activation in dendritic cells, which is required for their accumulation in the lymph node for T-cell priming. [26][27][28] More recently, DOCK8 was also shown to regulate macrophage migration through an interaction with LRAP35, linking Cdc42 to actomyosin dynamics. 29 Thus, in this context, DOCK8 can activate Cdc42, but also function as an adaptor/ scaffold molecule to link Cdc42 to the cytoskeleton.…”
Section: Dock8 Regulates Immune Synapse Formationmentioning
confidence: 99%